2017
DOI: 10.1016/j.lfs.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The level of effort, rather than muscle exercise intensity determines strength gain following a six-week training

Abstract: Aim This study investigated the effect of voluntary motor effort during a low-intensity (30% maximal voluntary contraction [MVC]) muscle exercise training program on increasing muscle strength. Materials and Methods Eighteen young and healthy individuals were randomly assigned to one of three groups: high mental effort (HME), low mental effort (LME), or a no-training control (CTRL) group. Training lasted for 6 weeks (15 min/day, 5 days/week). The participants’ right-elbow flexor muscle strength was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Table 1 presents details of each included article regarding sample, measures, and key results. The sample size of the MIT groups in the included studies ranged from 6 to 18, three studies with a sample size of 6 ( Leung et al, 2013 ; Yao et al, 2013 ; Jiang et al, 2017 ), two studies with a sample size of 8 ( Ranganathan et al, 2004 ; Bahari et al, 2011 ), two studies with a sample size of 9 ( Lebon et al, 2010 ; Grôspretre et al, 2017 ), nine studies with a sample size of 10 ( Yue and Cole, 1992 ; Sidaway and Trzaska, 2005 ; Fontani et al, 2007 ; Shackel and Standing, 2007 ; Wright and Smith, 2009 ; de Ruiter et al, 2012 ; Darvishi et al, 2013 ; Jiang et al, 2016 ; Bouguetoch et al, 2021 ), three studies with a sample size of 12 ( Cornwall et al, 1991 ; Reiser and Munzert, 2011 ; Goudarzian et al, 2017 ), one study with a sample size of 15 ( Mamone, 2013 ), three studies with a sample size of 16 ( Smith et al, 2003 ; Niazi et al, 2014 ; Alenezi, 2018 ), and one study with a sample size of 18 ( Herbert et al, 1998 ). All the selected studies included a non-exercise and/or a non-imagery control group.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents details of each included article regarding sample, measures, and key results. The sample size of the MIT groups in the included studies ranged from 6 to 18, three studies with a sample size of 6 ( Leung et al, 2013 ; Yao et al, 2013 ; Jiang et al, 2017 ), two studies with a sample size of 8 ( Ranganathan et al, 2004 ; Bahari et al, 2011 ), two studies with a sample size of 9 ( Lebon et al, 2010 ; Grôspretre et al, 2017 ), nine studies with a sample size of 10 ( Yue and Cole, 1992 ; Sidaway and Trzaska, 2005 ; Fontani et al, 2007 ; Shackel and Standing, 2007 ; Wright and Smith, 2009 ; de Ruiter et al, 2012 ; Darvishi et al, 2013 ; Jiang et al, 2016 ; Bouguetoch et al, 2021 ), three studies with a sample size of 12 ( Cornwall et al, 1991 ; Reiser and Munzert, 2011 ; Goudarzian et al, 2017 ), one study with a sample size of 15 ( Mamone, 2013 ), three studies with a sample size of 16 ( Smith et al, 2003 ; Niazi et al, 2014 ; Alenezi, 2018 ), and one study with a sample size of 18 ( Herbert et al, 1998 ). All the selected studies included a non-exercise and/or a non-imagery control group.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, combining the two practice methods simultaneously, patients could almost always activate not only the muscle but also the neural circuits controlling the motor action, adding a low-intensity actual movement execution exercise and/or cognitive training to NmES. Accordingly, the most recent studies suggest that cognitive training (i.e., motor imagery) alone ( 104 ), in addition to low-intensity strength training ( 105 ) or NmES ( 106 ), has a beneficial effect on strength increase in both the symptomatic and asymptomatic populations ( 107 , 108 ). Thus, Jiang et al ( 109 ) reported that at the end of a 12-week training of healthy elderly subjected to both high-intensity physical exercise and high mental effort (HME), elbow flexion strength was significantly increased compared to the control group, with no significant difference between the exercise-only and HME groups.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study concluded that level of effort involved in resistance exercise training plays a critical role in determining the amount of strength augmentation. 16 . It is well known that acute or chronic increases in physical activity result in structural, metabolic, hormonal, neural, and molecular adaptations that increase the level of force or power that can be sustained by a muscle.…”
Section: Discussionmentioning
confidence: 99%